Evolution of the Kuiper belt during the accretion of the outer planets - Brunini, Adrián (2002)
A set of self-consistent simulations of the formation of Uranus and Neptune are performed to study the evolution of the native KBOs in the process. Our main goal is to have a deeper understanding of the impact of the formation of the outer planets on the present orbital structure of the trans-neptunian region. We aim to understand if resonance capture driven by the outward migration of Neptune can actually occur and its interplay with the invasion of massive planetesimals expelled from the Uranus-Neptune region as a byproduct of their formation. Also the putative present existence in the Oort reservoir of a population of objects originated in the Kuiper belt is analyzed.